Australian Healthcare Professionals’ Knowledge of and Attitudes toward Binge Eating Disorder - Cain, Belinda; Buck, Kimberly; Fuller-Tyszkiewicz, Matthew; Krug, Isabel (Frontiers in Psychology, 2017)
Objective: This study aimed to investigate Australian healthcare practitioners’ knowledge and attitudes towards binge eating disorder (BED). Method: Participants were 175 healthcare professionals, who were randomized to one of two conditions that assessed diagnostic and treatment knowledge of either comorbid BED and obesity or only obesity via case vignette, as well as weight bias towards obese patients. Results: Results suggested that participants demonstrated a reluctance to diagnose comorbid BED and obesity, that their knowledge of physical complications associated with BED was limited, and that they indicated a narrow range of evidence-based treatment options. When compared with levels of weight bias expressed by healthcare professionals in previous international studies, Australian clinicians were significantly less biased, however, still largely endorsed ‘negative’ attitudes towards obesity. Conclusions: Findings suggest that future clinical training in eating disorders should therefore focus not only on diagnostic criteria, physical complications and treatment options, but also on practitioner attitudes towards eating and weight.